Computation is Existence — A Brief Overview of the Multi-faceted Implications of Quantum Mechanical Description of Black holes as hyper computational Entities - Patra, Dr. Indrajit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article attempts to deal with the newly emerging paradigm of black hole computers in which adopting a quantum-mechanical perspective of information enables us to assess the computational power of black holes. Viewing space-time itself as a computational entity and black holes as the supreme forms of serial computers can help us to gain insight into the ideas from gravitational thermodynamics and the emergent nature of space-time and gravity. The idea of black holes as computational entities also relates to quantum gravity which views space-time and foamy and fuzzy due to quantum fluctuations and divided into discrete, Planck-scale blocks.